Forensic Analysis of YAFFS2 - Zimmermann, Christian; Spreitzenbarth, Michael; Schmitt, Sven; Freiling, Felix (Proceedings of GI Sicherheit 2012, 2012)
In contrast to traditional file systems designed for hard disks, the file systems used within smartphones and embedded devices have not been fully analyzed from a forensic perspective. Many modern smartphones make use of the NAND flash file system YAFFS2. In this paper we provide an overview of the file system YAFFS2 from the viewpoint of digital forensics. We show how garbage collection and wear leveling techniques affect recoverability of deleted and modified files. <br
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.lehrst.forens_0